Iron, siderophores, and the pursuit of virulence: independence of the aerobactin and enterochelin iron uptake systems in Escherichia coli. - Williams, P H (1986)
Many strains of Escherichia coli isolated from extraintestinal infections of humans and domestic animals are able to synthesize two siderophores, aerobactin and enterochelin. Although aerobactin has a dramatically lower affinity for iron than enterochelin, it has been shown to provide a significant selective advantage for bacterial growth in conditions of iron limitation, such as in the body fluids and tissues of an infected animal. We have used streptonigrin, which is bactericidal in the presence of iron, as a probe to determine levels of free intracellular iron during bacterial growth promoted by the two siderophores. A strain with only enterochelin remained sensitive to the bactericidal action of streptonigrin, suggesting that assimilated iron was contributed to an intracellular pool from which the rate of its withdrawal for growth is probably concentration dependent. On the other hand, a strain that synthesized aerobactin alone became resistant to streptonigrin, indicating that iron complexed with aerobactin was not made accessible to streptonigrin and suggesting that it may be channeled directly to where it is required for growth. Aerobactin, probably because it is repeatedly reusable, efficiently stimulated bacterial growth at external concentrations some 500-fold lower than those of enterochelin. Moreover, the effective concentration, and thus the siderophore activity, of enterochelin but not of aerobactin was significantly reduced by the presence of human serum in the medium. Differential regulation of the genetic determinants of the two siderophores resulted in preferential induction of the aerobactin system in the presence of unsaturated levels of transferrin and lactoferrin.